2022
DOI: 10.1007/s12010-021-03790-8
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Inhibitors from Nigella Sativa

Abstract: The recently encountered severe acute respiratory syndrome coronavirus 2 creates huge predicaments among various countries. Lack of specific treatment of COVID-19 disease demands urgency in drug design against SARS-CoV-2 targets. Nigella sativa the miraculous herb native to South and Southwest Asia and belonging to the family Ranunculaceae, due to its beneficial bioactive properties, was used by us for performing in silico study to analyze the potential of its compounds so that they can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As sterols interact with the active site, they can be promising candidates, particularly oxygenous tetrahydroxy sterol, which has a high tendency to form hydrogen bonds. Schiff base ligands have been shown to inhibit M pro in previous studies [ 54 ] as well as caffeine [ 54 , 55 ], nethylxanthines [ 56 ], natural product isolates [ 57 ], glycyrrhizin [ 58 ], ML188 [ 59 ], pyrimidonic and pyridonic pharmaceuticals [ 60 , 61 ], kaempferol [ 62 ], fungal natural products [ 63 ], marine natural compounds [ 64 ], Ceftazidime [ 65 ], hepatitis C virus protease drugs [ 66 ], and other inhibitors [ 67 , 68 , 69 , 70 , 71 , 72 ]. In our molecular docking study, these natural compounds were identified as potential M pro inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…As sterols interact with the active site, they can be promising candidates, particularly oxygenous tetrahydroxy sterol, which has a high tendency to form hydrogen bonds. Schiff base ligands have been shown to inhibit M pro in previous studies [ 54 ] as well as caffeine [ 54 , 55 ], nethylxanthines [ 56 ], natural product isolates [ 57 ], glycyrrhizin [ 58 ], ML188 [ 59 ], pyrimidonic and pyridonic pharmaceuticals [ 60 , 61 ], kaempferol [ 62 ], fungal natural products [ 63 ], marine natural compounds [ 64 ], Ceftazidime [ 65 ], hepatitis C virus protease drugs [ 66 ], and other inhibitors [ 67 , 68 , 69 , 70 , 71 , 72 ]. In our molecular docking study, these natural compounds were identified as potential M pro inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…When the expression of GSK3B increases, it will simultaneously increase the expression of IL6 and TNF. Studies showed that the upregulation of inflammatory factors such as IL6, IL1B, and TNF reduced the expression of ACE2 [ 58 ], while the latest SARS-CoV-2 virus did not. Therefore, taking oral preparations made from SAIN or the single-use of Jaceosidin can effectively prevent SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…[44] However, the binding energy to viral proteins has been low. [45] Colorimetric tests revealed the presence of toxic effects of alloaromadendrene component on breast cancer cells in 96-hour applications. On the other hand, the compound, which is also known to cause repellent activity is also reported to have larvicidal activity.…”
Section: Chemical Composition Of Thuja Orientalismentioning
confidence: 99%